Pengaruh Pendapatan Asli Daerah, Dana Alokasi Umum dan Dana Alokasi Khusus terhadap Tingkat Kemandirian Keuangan Daerah pada Kabupaten Banyuwangi Tahun 2012 - 2016 - Novi Theresia Kiak; Septina Nuro (OECONOMICUS Journal of Economics, 2018)
The implementation of regional autonomy is not only focused on central grants in the form of balancing funds. The regions can be self-sufficient to take care of their own households including local financial independence by utilizing and utilizing, and managing the potentials in the regions in order to improve public services to the community and regional development. The purpose of this research is to know whether there is influence of Local Original Income (PAD), General Allocation Fund (DAU) and Special Allocation Fund (DAK) to the level of Financial Independence of Banyuwangi Regency either partially or simultaneously. The population in this research is Banyuwangi Regency using secondary data in the form of Budget Realization Report (BRR) of Banyuwangi Regency in 2012 - 2016. Hypothesis testing in this research use multiple linear regression with t test, F test and coefficient of determination. The data that have been collected is analyzed first by testing the classical assumption then hypothesis tested by SPSS 20.0.